PENERAPAN MODEL PEMBELAJARAN EKSPERIMEN BERBASIS GROWTH MINDSET TERHADAP PEMAHAMAN KONSEP WARNA TERSIER MURID KELAS III SD NEGERI 03 PANCOR - Putri Niva Nurviani; Lalu Parhanuddin; Syamsul Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The understanding of tertiary color concepts among elementary school students remains relatively low because the learning process tends to be teacher-centered and provides limited direct learning experiences. In addition, the implementation of learning activities that foster students’ growth mindset has not been optimized. This study aimed to determine the implementation of an experiment-based learning model integrated with a growth mindset approach on students’ understanding of tertiary color concepts in Grade III of SD Negeri 03 Pancor. This research employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest-Posttest Design. The participants consisted of 27 third-grade students of SD Negeri 03 Pancor. Data were collected through tests and observations. The tests were used to measure students’ understanding of tertiary color concepts before and after the treatment, while observations were conducted to assess students’ growth mindset during the learning process. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed Rank Test. The results showed that the mean pretest score of 53.52 increased to 80.93 on the posttest. The Wilcoxon Signed Rank Test indicated a significance value of 0.000 (p < 0.05), demonstrating a significant difference between the pretest and posttest scores after the implementation of the experiment-based learning model with a growth mindset approach. Observation results also revealed that students’ growth mindset reached 86.34%, which was categorized as very high. Therefore, the experiment-based learning model integrated with a growth mindset approach was effective in improving students’ understanding of tertiary color concepts in Grade III of SD Negeri 03  Pancor.